Cretney and Probert's family law - Probert, Rebecca 1973- (Sweet & Maxwell, 2012)
This 8th edition cuts through the black letter law to provide students with guidance on all the major themes and principles of family law, covering both formal and informal relationships
Previous ed.: 2009
Includes bibliographical references and index
Keywords: Domestic relations / England; Domestic relations / Wales